Aortic annular measurements in fresh post-mortem hearts: a study in Sri Lankans - Udhayakumar, S.; Yasawardene, S. G. (Ceylon Medical Journal, 2015)
Attached

The basal aortic root measurements were determined in 320 fresh, autopsied, normal, adult, Sri Lankan hearts collected from the Judicial Medical Office, National Hospital of Sri Lanka. The correlation between the measurements and demographic data of the individual was calculated. The mean aortic root circumference at the basal ring was 64.7 mm ± 7SD (males 66.0mm ± 6.4SD, females 58.0mm ± 6.1SD) and calculated aortic annular diameter was 20.60mm ± 2.2SD (males 21.02mm ± 2.0SD, females 18.47mm ± 1.9SD). Mean circumference showed significant gender difference. Significant positive correlation was seen between the age and aortic root circumference. We describe the normal range of aortic root diameters in healthy adult autopsied Sri Lankans. The values are smaller in Sri Lankans compared to Caucasians.
Keywords: basal aortic annular diameter; basal aortic root circumference; demographic data; fresh post mortem